2014
DOI: 10.1159/000363202
|View full text |Cite
|
Sign up to set email alerts
|

Statins for the Prevention of Contrast-Induced Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a common medical problem, especially in patients undergoing cardiovascular procedures. The risk of kidney damage has multiple determinants and is often related to or exacerbated by intravenous or intra-arterial iodinated contrast. Contrast-induced AKI (CI-AKI) has been associated with an increased risk of subsequent myocardial infarction, stroke, the development of heart failure, rehospitalization, progression of chronic kidney disease, end-stage renal disease, and death. Statins h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This tubular toxicity has been reported in rare case reports, sometimes associated with tubulointerstitial nephritis . Nevertheless, randomized trials have shown that statins may also have renoprotective effects, especially in diabetic patients, even when prescribed at high doses, or when given for prevention of contrast‐induced AKI . Of note, a meta‐analysis showed similar renoprotective effects in high CVD risk patients treated with atorvastatin and rosuvastatin prescribed at commonly used doses .…”
Section: Discussionmentioning
confidence: 86%
“…This tubular toxicity has been reported in rare case reports, sometimes associated with tubulointerstitial nephritis . Nevertheless, randomized trials have shown that statins may also have renoprotective effects, especially in diabetic patients, even when prescribed at high doses, or when given for prevention of contrast‐induced AKI . Of note, a meta‐analysis showed similar renoprotective effects in high CVD risk patients treated with atorvastatin and rosuvastatin prescribed at commonly used doses .…”
Section: Discussionmentioning
confidence: 86%
“…[3,[12][13][14] In a study, Tai et al [12] created an experimental model with bilateral kidney I/R injury and examined cardiac function. They found that kidney I/R injury was associated with cardiac dysfunction and niacin reduced myocardial oxidative stress using indicators such as serum troponin, urea, creatinine, and malondialdehyde.…”
Section: Discussionmentioning
confidence: 99%
“…However, kidney TNF-a immunoreactivity in I/R+CIL+ROS group was found to be significantly increased, compared to the control Statins have preventive effects on myocardial and kidney injury, following ischemic and inflammatory processes such as acute coronary syndrome, percutaneous coronary intervention, and cardiovascular surgery. [14,[19][20][21][22] Several studies have shown that atorvastatin and rosuvastatin protects kidney, improving glomerular filtration rate and reducing proteinuria, and atorvastatin may even be more effective in reducing proteinuria. [23] In a study, the rats were subjected to 30 min myocardial ischemia, following an 18-hour intraperitoneal rosuvastatin at a dose of 0.1 to 5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing decrease in renal blood flow may exceed 50% and last for some hours causing an ischaemic and ultimately severe reperfusion injury [87]. Statins have been shown to decrease this risk in a number of studies and meta-analyses [88][89][90][91][92]. The presumed benefit of short term, sometimes high intensity statin use is thought to be conferred by an improvement in renal perfusion secondary to the effects of statins on the production of NO.…”
Section: 2mentioning
confidence: 99%